Effect of integrated reporting and environmental reputation on comprehensive decision-making non-professional investors - Widyatama, Arif; Agustia, Dian; Ardianto, Ardianto; Soewarno, Noorlailie (Business: Theory and Practice, 2023)
This study is to examine the effect of integrated reporting and environmental reputation on the comprehensive decision-making by non-professional investors. Specifically, this study examines the process investors use to make comprehensive decisions (i.e. acquisition, evaluation, weighting, and judgment) when seeing information about companies’ integrated reporting and environmental reputations. We use a web-based experiment, or 2x3 between-subjects design, to investigate whether companies’ integrated reporting and environmental reputations have any influence on non-professional investors’ comprehensive decision making. 157 participant randomly selected students to serve as surrogate investors in this experiment. The data obtained were then tested using ANOVA and followed by a post hoc test. The findings show that companies that provide integrated reporting and have an environmental reputation make it easier for non-professional investors to make comprehensive decisions. Research on integrated reporting is scarce. There has been some research on the relationship between integrated reporting and investment decision making, but the environmental reputation of the relationship between integrated reporting and investment decisions has not been extensively explored. In fact, environmental issues are global issues. Furthermore, we argue that this research is very important to be carried out in Indonesia, considering that the arrangements regarding the presentation of various information can be carried out in an integrated or separate manner. This study can provide suggestions for regulators about the importance of regulations regarding the obligation to present financial and non-financial information in an integrated manner.